2012
DOI: 10.1007/s00234-012-1047-3
|View full text |Cite
|
Sign up to set email alerts
|

Italian multicenter experience with flow-diverter devices for intracranial unruptured aneurysm treatment with periprocedural complications—a retrospective data analysis

Abstract: Our retrospective study confirms that morbidity and mortality rates in treatment with FDD of unruptured wide-neck or untreatable cerebral aneurysms do not differ from those reported in the largest series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
101
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 30 publications
(31 reference statements)
3
101
1
5
Order By: Relevance
“…8,14 Treatment of fusiform aneurysms with endovascular flow diversion has been limited to a discussion in small case series or as a subgroup in larger series of all aneurysm types. 2,4,7,17,19,21 In a series by Siddiqui et al, 22 7 patients underwent flow diversion for large or giant fusiform vertebro- basilar aneurysms. The PED was used in 6 patients, and the Silk (Balt Extrusion) device was used in 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 Treatment of fusiform aneurysms with endovascular flow diversion has been limited to a discussion in small case series or as a subgroup in larger series of all aneurysm types. 2,4,7,17,19,21 In a series by Siddiqui et al, 22 7 patients underwent flow diversion for large or giant fusiform vertebro- basilar aneurysms. The PED was used in 6 patients, and the Silk (Balt Extrusion) device was used in 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another review and meta-analysis of flow diversion demonstrated an all-comer late complication rate of 2.4%. 22 Few studies have subset analyses specific to cavernous segment aneurysms, but in a multicenter Italian study, Briganti et al 23 reported a 4% mortality rate for treatment of cavernous segment aneurysms with flow diverters, but this comprised 3 total cases (of 76): Two patients experienced fatal ICA thrombosis, and the other experienced a fatal ICA perforation, all during treatment of giant cavernous aneurysms. The mortality rate reported in the Italian study differs from that in both the subset analysis in the recent Canadian study 12 and in this series (both with 0% overall morbidity and mortality, 70 total combined cavernous aneurysms).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The bare metal construct of the PED serves as a scaffold for neointimal proliferation, thereby excluding the aneurysm sac from the parent artery. 5,6 A number of previous studies have demonstrated that the PED is associated with high rates of aneurysm occlusion with relatively low complication rates.…”
mentioning
confidence: 99%